Identidades e espaços: as representações de Cleópatra e do Egito em Vida de Antônio, de Plutarco - Mello, Felipe Aiala de (2019)
This dissertation aims to analyze the representations of Cleopatra and the Egypt created by Plutarch in his book Life of Antony. In the Roman general biography, Plutarch registers his vision of the queen of Egypt and the East. From an ideologically marked point of view of a citizen from a Greek polis (Chaeronea) who lived under Roman control, Plutarch narrates his vision of the East, (re)configures facts, data, in short, his own history with a biographical, documentary and historical writing but strategically, at the same time, dramatic, theatrical, emotional and moralizing. This research intends to show that Plutarch, by composing the image of Cleopatra and the representation of Egypt, does so from an imperialistic and orientalist perspective, in conformity with the Roman version of the facts. The main analytical categories used to achieve this dissertation are, mainly, imperialism, orientalism, romanization and representation/identity. The theoretical tools, as well as the selected authors and texts, offer the necessary epistemological basis to support the analytical procedures and allow to develop some points of view on the chosen corpus. The methodology used to develop the analysis is based on the traditional form of historiographer work, that is, the internal and external critiques of the sources, combined with the contents analysis. Plutarch, from the stereotypical oppositional dichotomies sustained by the moralistic and moralizing ideologies, subdues the Queen of Egypt and the East, in favor of a supposed superiority based on a cultural and moral hierarchy, in agreement with Roman propaganda.